The Digitalization of Sound: How the Consumption of Music Changed from Vinyl to Hybrid Experiences - De Notaris, Dario; Savonardo, Lello (Italian Sociological Review, 2022)
This paper focuses on how digital media and new technological devices have changed music production and consumption processes. The role of music will be discussed as a collective process fed by individual consumption through personal media, starting from a sociological analysis of the main technological evolution in its industry field. This is related to the widespread use of devices to play music at home and also on the move. From the creation of the gramophone to the Walkman, from iPods to Smartphones, music consumption has become much more liquid. Production processes have changed, moving from recording studios managed by expert composers to easy-to-use devices that enable anyone to become a digital artist. Additionally, social media represent new ways to create and share original and creative works. Today, artificial intelligence, deep learning and holographic systems introduce new innovative perspectives to create, consume, and share music.